2016
DOI: 10.1371/journal.pone.0167234
|View full text |Cite|
|
Sign up to set email alerts
|

16 Weeks of Progressive Barefoot Running Training Changes Impact Force and Muscle Activation in Habitual Shod Runners

Abstract: Short-term effects of barefoot and simulated barefoot running have been widely discussed in recent years. Consequences of adopting barefoot running for a long period, including as a training approach, still remain unknown. The present study evaluated the influence of 16 weeks of progressive barefoot running training on impact force and muscle activation in habitual shod runners. Six habitual shod runners (3 men and 3 women, 29.5 ± 7.3 years) were tested barefoot (BF) and shod (SH), before and after 16 weeks of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 62 publications
0
10
1
1
Order By: Relevance
“…The most common approach to the analysis of sEMG signals is the assessment of the maximum or mean amplitude of the envelope, with or without normalisation to the maximum voluntary contraction [ 71 – 74 , 76 87 , 89 95 , 97 – 106 ]. The analysis of timing is also common in sport science, with usual approaches ranging from the detection of the onset and offset of sEMG activity and global and local maxima detection to examination of the entire time course using statistical parametric mapping [ 72 – 74 , 76 79 , 81 , 83 , 89 93 , 96 , 100 , 102 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common approach to the analysis of sEMG signals is the assessment of the maximum or mean amplitude of the envelope, with or without normalisation to the maximum voluntary contraction [ 71 – 74 , 76 87 , 89 95 , 97 – 106 ]. The analysis of timing is also common in sport science, with usual approaches ranging from the detection of the onset and offset of sEMG activity and global and local maxima detection to examination of the entire time course using statistical parametric mapping [ 72 – 74 , 76 79 , 81 , 83 , 89 93 , 96 , 100 , 102 ].…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the studies included the recordings of less than nine muscles [ 72 , 73 , 77 85 , 87 , 91 95 , 98 – 106 , 158 ], while only a few considered a number between nine and 16 [ 74 , 76 , 86 , 88 , 90 , 96 ] or bigger than 16 [ 71 , 97 ]. Most of the studies considered muscles of the lower limb [ 71 73 , 77 , 78 , 81 , 83 85 , 89 , 90 , 92 , 93 , 95 , 96 , 98 , 104 , 106 , 115 ], with the remaining focussing on the trunk and/or upper limb [ 74 , 76 , 80 , 82 , 87 , 94 , 100 , 102 , 103 , 106 ] or both the upper and lower body [ 79 , 86 , 88 , 91 , 97 , 99 , 101 ]. Bilateral recordings (involving the left and right hand side of the same muscles) were less common [ 71 , 74 , 77 , 82 , 86 , 88 , 90 , 97 , 98 , 101 ] than ipsilateral [ 72 , 7...…”
Section: Resultsmentioning
confidence: 99%
“…Whether the continued usage of the highly cushioned shoes over a longer adaptation period would have changed the lower extremity kinematics is unknown. Studies indicate that habituation into barefoot running or minimalist shoes running can change running biomechanics (Azevedo, Mezencio, Amadio, & Serrao, 2016). Although no study on habituation has been done using highly cushioned shoes, it may be worthwhile to investigate the habituation effects of highly cushioned shoes on running biomechanics over a longer period of time.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies [ 19 , 20 ] however, did not observe any relationships between the foot arch structure and the performance in sprinting, jumping and balancing. Another possible reason for the differences in motor skills between both populations may be different adaptations of muscle strength to regular physical activities with or without footwear [ 19 , 21 , 22 ]. One study [ 23 ] showed that foot muscle strength is associated with sprinting and jumping skills in preschool-age children.…”
Section: Discussionmentioning
confidence: 99%